Are Tents a “Home”? Extending Section 8 Privacy Rights for the Precariously Housed - Ferencz, Sarah; Blomley, Nicholas; Flynn, Alexandra; Sylvestre, Marie-Eve (McGill Law Journal / Revue de droit de McGill, 2022)
The home, for most of us, is an obvious zone to assert privacy and property rights. This is not the case for those whose control of residential space is precarious. Our article focuses on privacy rights under the Canadian Charter of Rights and Freedoms for those living in tents and, specifically, the judicial rejection of the tent as a home garnering legal protection under section 8. We focus on a 2018 case from British Columbia, R v. Picard, the only judicial decision that we could locate that has explored this question. In holding that the tent is not a home, Picard draws from the venerable castle doctrine—the legal principle that cements enhanced legal protection for the home. Drawing from legal geography, we argue that the castle doctrine is grounded in a particular legal-spatial imaginary, such that the home is represented in its ideal form as a privately owned detached dwelling. The connection between privacy rights and the home, as reflected in jurisprudence, is grounded in property rights that formally excluded all but white men in colonial North America and continues to be linked to systemic inequality. The exclusion of those living in tents and other forms of precarious housing from exercising enhanced privacy rights afforded to the home exacerbates existing inequalities, as the most vulnerable are unable to benefit from legal protections of the home. We conclude that the denial of tents as homes is legally flawed and should be reconsidered in future jurisprudence.